2013
DOI: 10.1186/1741-7015-11-52
|View full text |Cite
|
Sign up to set email alerts
|

Association of fascin-1 with mortality, disease progression and metastasis in carcinomas: a systematic review and meta-analysis

Abstract: BackgroundFascin-1 is an actin-bundling protein expressed in many human carcinomas, although absent from most normal epithelia. Fascin-1 promotes filopodia formation, migration and invasion in carcinoma cells; in mouse xenograft tumor models it contributes to metastasis. Fascin-1 is an interesting candidate biomarker for aggressive, metastatic carcinomas but data from individual studies of human tumors have not yet been pooled systematically.MethodsThis systematic review was conducted in accordance with PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
168
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(177 citation statements)
references
References 63 publications
9
168
0
Order By: Relevance
“…Elevated fascin expression is associated with increased risk of metastasis and mortality from patient studies, and increased numbers of filopodia are correlated to increased invasiveness, aggressivity and decreased survival rate 17,18,30 . To develop therapeutics for metastatic cancer treatment, we developed an HTS method, screened chemical libraries and identified smallmolecule compounds that specifically inhibit the actin-bundling function of fascin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated fascin expression is associated with increased risk of metastasis and mortality from patient studies, and increased numbers of filopodia are correlated to increased invasiveness, aggressivity and decreased survival rate 17,18,30 . To develop therapeutics for metastatic cancer treatment, we developed an HTS method, screened chemical libraries and identified smallmolecule compounds that specifically inhibit the actin-bundling function of fascin.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of 26 immunohistochemical studies (total B9,000 patients) of the five prevalent human carcinomas (breast, colorectal, gastric, lung and oesophageal carcinomas) revealed that, in breast, colorectal and oesophageal carcinomas, high levels of fascin are associated with increased risk of mortality and disease progression 30 . Pooled analysis of all carcinomas indicate that high levels of fascin are associated with increased risk of mortality, lymph node metastasis and distant metastasis, and may provide a novel biomarker for early diagnosis of aggressive and metastatic tumours 30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The additional forms of fascin, fascin-2 and -3, are expressed in retinal photoreceptor cells and the testes, respectively (16). Published data has demonstrated that fascin is upregulated or highly expressed in the human cancer of various organs, including the oesophagus (17), breast (18), colon (19), lung (20), stomach (21) and urinary bladder (22), as well as in individual tissues, and that the expression of fascin is associated with aggressive behaviour (23). Previous studies of breast cancer have identified that fascin overexpression is associated with factors representing aggressive tumor behaviour, for example hormonal receptor negativity, a triple-negative subtype and/or a basal-like phenotype (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%